The Use of Collective Intelligence to Create Efficient Marketing Strategies - Adnane Derbani; Ade Banani (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2020)
There is no doubt that almost all companies recognized the necessity and the significant role of marketing strategies in the development and the progress of any business. However, the challenge still is how to elaborate and create effective marketing strategies? The purpose of this study is to investigate and illustrate how we could create efficient marketing strategies by using the Collective Intelligence approach? Interviews were conducted with marketing department teams; added to participants from other department members and also customers and stakeholders. through three different steps (before, during, and after the use of this approach); in order to provide and discover the feedbacks and results of all participants through the implementation of the Collective Intelligence approach. Following the result; There is a consensus from the participants of this research study confirmed that the use of this new concept of collective intelligence will not only transform the design of the future trajectory of elaboration of marketing strategies but also the future of work.